gammaCOP is required for apical protein secretion and epithelial morphogenesis in Drosophila melanogaster. - Grieder, N.C.; Caussinus, E.; Parker, D.S.; Cadigan, K.; Affolter, M.; Luschnig, S. (PLoS ONE, 2008)
There is increasing evidence that tissue-specific modifications of basic cellular functions play an important role in development and disease. To identify the functions of COPI coatomer-mediated membrane trafficking in Drosophila development, we were aiming to create loss-of-function mutations in the gammaCOP gene, which encodes a subunit of the COPI coatomer complex.We found that gammaCOP is essential for the viability of the Drosophila embryo. In the absence of zygotic gammaCOP activity, embryos die late in embryogenesis and display pronounced defects in morphogenesis of the embryonic epidermis and of tracheal tubes. The coordinated cell rearrangements and cell shape changes during tracheal tube morphogenesis critically depend on apical secretion of certain proteins. Investigation of tracheal morphogenesis in gammaCOP loss-of-function mutants revealed that several key proteins required for tracheal morphogenesis are not properly secreted into the apical lumen. As a consequence, gammaCOP mutants show defects in cell rearrangements during branch elongation, in tube dilation, as well as in tube fusion. We present genetic evidence that a specific subset of the tracheal defects in gammaCOP mutants is due to the reduced secretion of the Zona Pellucida protein Piopio. Thus, we identified a critical target protein of COPI-dependent secretion in epithelial tube morphogenesis.These studies highlight the role of COPI coatomer-mediated vesicle trafficking in both general and tissue-specific secretion in a multicellular organism. Although COPI coatomer is generally required for protein secretion, we show that the phenotypic effect of gammaCOP mutations is surprisingly specific. Importantly, we attribute a distinct aspect of the gammaCOP phenotype to the effect on a specific key target protein.